ANALISIS KESELAMATAN DAN KESEHATAN KERJA PADA PEMERIKSAAN DAN PENGUJIAN GENERATOR SET - Atidira Dwi Hanani; I. G. Nazaruddin (LLDIKTI Wilayah X, 2023)
PT. IAK is an occupational safety and health (OSH) service company that conducts inspections and tests of various equipment, one of which is a Generator Set (Genset). The need to use generators in various places makes inspection and testing of generators often carried out. In the work of inspecting and testing generators, there are potential hazards that can be experienced by workers. Therefore, this study aims to analyze the risks of OSH in generator inspections at PT. IAK. This is a qualitative research. Data obtained through triangulation methods consisting of interviews, observation and documentation. Data analysis was performed using the Job Safety Analysis method. The results showed that the stages of work in the generators inspection and testing activities consisted of equipment preparation, LOTO installation and generator MCCB isolation, pre-inspection, inspection and testing, final inspection, and cleaning of tools or service equipment. Each stage of work has the potential for work-related accidents and diseases that can occur if workers are not careful or do not comply with established procedures. Prevention recommendations are ensuring the correct working position, storing equipment in its place, installing and lifting equipment properly, and using tools and personal protective equipment according to the type of work.Keywords: safety; health; generator set